2017
DOI: 10.1186/s12967-017-1182-z
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated CD40L gene transfer increases Teffector/Tregulatory cell ratio and upregulates death receptors in metastatic melanoma patients

Abstract: Background and aimsMalignant melanoma is an aggressive tumor sensitive for immunotherapy such as checkpoint blockade antibodies. Still, most patients with late stage disease do not respond, and the side effects can be severe. Stimulation of the CD40 pathway to initiate anti-tumor immunity is a promising alternative. Herein, we demonstrate immune profiling data from melanoma patients treated with an adenovirus-based CD40 ligand gene therapy (AdCD40L).MethodsPeripheral blood mononuclear cells and plasma were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 44 publications
0
24
0
2
Order By: Relevance
“… 16 Accordingly, the virus ICOVIR17K-iRGD might be more effective in clinical studies in which the replication will be more efficient than in the mouse model. Finally, immunovirotherapy may confer benefit to other strategies aimed at inducing anti-tumor immune responses, such as CD40L costimulation, 17 bispecific T cell engagers (BiTEs), 18 incorporation of immunostimulatory genes such as interleukin-12 (IL-12), 19 or checkpoint inhibitors. 20 …”
Section: Discussionmentioning
confidence: 99%
“… 16 Accordingly, the virus ICOVIR17K-iRGD might be more effective in clinical studies in which the replication will be more efficient than in the mouse model. Finally, immunovirotherapy may confer benefit to other strategies aimed at inducing anti-tumor immune responses, such as CD40L costimulation, 17 bispecific T cell engagers (BiTEs), 18 incorporation of immunostimulatory genes such as interleukin-12 (IL-12), 19 or checkpoint inhibitors. 20 …”
Section: Discussionmentioning
confidence: 99%
“…29 Part of this phenomenon might not be a direct effect of CD40 signaling, but of secondary upregulation of death receptors on susceptible cell types. 30 However, some clinical effect of the anti-CD40 antibodies lucatumumab and dacetuzumab has been shown against B cell malignancies, which could be attributed to antibody-mediated phagocytosis by macrophages and induction of antibodydependent cytotoxicity (ADCC). 31 Following ligation of CD40, tumor cells show signs of DNA damage, secrete pro-angiogenic factors, like VEGF and IL-8, and generally adopt a state reflecting a senescence-associated secretory phenotype (SASP) due to CD40-induced NFκB activation.…”
Section: Cd40/cd40l Relevance For Cancer Immunotherapymentioning
confidence: 99%
“…Additional developments in both the delivery method and the format of CD40L have also shown promise. 30,56,[61][62][63]…”
Section: Cd40l-based Cellular and Gene Therapymentioning
confidence: 99%
“…AdCD40L is a replication-deficient adenovirus carrying the gene for CD40 ligand (CD40L) [ 6 ]. We have previously shown that AdCD40L therapy can be used safely in patients with MM [ 6 ] and that the T cell to T regulatory cell ratio is significantly enhanced post treatment [ 7 ]. The first cohort of patients received four intratumoral injections of AdCD40L and the following cohort received four to eight AdCD40L injections combined with low dose cyclophosphamide conditioning.…”
Section: Introductionmentioning
confidence: 99%